Assessment on level of selected metals and proximate composition of raw cow milk samples from selected sites of Bahir Dar City and it's surrounding - Yetinebersh Shitahun; Minbale Endaye; Adane Kassa (Food Chemistry Advances)
This study systematically assessed the concentrations of selected metals and the proximate composition of milk samples collected from six locations: Agerie Milk Cooperative, Andassa Livestock Research Center, Tekelehymanot Monastery, the College of Agriculture and Environmental Sciences, Bahir Dar Dairy Cooperative, and households in Keble-7, Bahir Dar city. Proximate composition, including moisture, ash, protein, and fat, was determined using the Kjeldahl digestion and Gerber methods, while metal analysis was performed using the Inductively Coupled Plasma Optical Emission Spectroscopy technique. The findings revealed significant variations (P<0.05) in both metal concentrations and proximate composition among the milk samples from the different sites. The average concentrations of detected metals were 1550.42 ± 34.76 mg/L for calcium (Ca), 137.26 ± 2.89 mg/L for magnesium (Mg), 23.97 ± 2.02 mg/L for iron (Fe), 1.10 ± 0.11 mg/L for copper (Cu), 40.48 ± 3.03 mg/L for zinc (Zn), 0.32 ± 0.01 mg/L for manganese (Mn), and 0.58 ± 0.05 mg/L for chromium (Cr). Lead (Pb), nickel (Ni), and cadmium (Cd) were not detected in any of the samples. All detected metal levels, except for iron, were below the permissible limits set by the World Health Organization (WHO). The mean proximate composition of the milk samples included moisture at 87.56 ± 1.16%, ash at 0.75 ± 0.04%, protein at 3.24 ± 0.34%, and fat at 4.02 ± 0.38%. These values were consistent with Food and Agriculture Organization (FAO) standards and aligned with findings from previous studies. Based on the findings, milk from these locations is safe for consumption, free from harmful levels of heavy metals, and provides nutritional benefits due to its favorable proximate composition.